Hb Knossos: HBB:c.82G>T Associated with HBB:c.315+1G>A Beta Zero Mutation Causes Thalassemia Intermedia - Nasouhipur, Hengameh (Springer India, 2014)
β-thalassemia is the most common single gene disorder worldwide and in Iran. In the present study we report for the first time a rare variant of hemoglobin HBB:c.82G>T; Codon 27 GCC→TCC (Ala→Ser), Hb Knossos, using sequencing and reverse dot blot hybridization, in members of a family from North Iran. The family has a 16 years-old compound heterozygous thalassemia intermedia male child presenting this variant together with HBB:c.315+1G>A (IVSII-I) mutation. The father, heterozygous for Hb Knossos, showed borderline hematological indices. To our knowledge, this is the first report of Hb Knossos in trans with the β(O) IVSII-I allele leading to thalassemia intermedia. Our data also highlight the necessity of deep molecular characterization of subjects presenting normal HbA2 level associated with abnormal or borderline red cell indices.